Ain (Terminalia tomentosa Wight & Arn.) a multipurpose tree for Konkan region of Maharashtra - Thaware, B.L.; Bhagat, S.B.; Khadtar, B.S. (Indian Journal of Agroforestry, 2020)
In Konkan region of Maharashtra Ain (Terminalia tomentosa) is a dominant tree species. An experiment was conducted in RBD with 7 replications during kharif 1991 with view to study the effect of pruning of branches on growth of Ain. Twelve trees were planted in each treatment per replication at 2 x 2 m spacing. The treatments comprised of no pruning, 50% pruning of branches and 100% pruning of branches. The observations were recorded during the year 2002 to 2004. The treatment differences were found to be statistically non significant. The height, dbh and branches were found to be slightly higher in pruning than the control (no pruning). Weight of leaves and branches obtained by pruning was higher in the 100% pruning than 50% pruning of branches. Thus, considering the regeneration ability, the 100% branches of trees may be pruned every year to obtain leaves as fodder for animals and branches for fuel wood.